2014
DOI: 10.9790/0853-13820914
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical Study of Various Shapes of Mandibular Coronoid Process in Relation to Gender &Age

Abstract: Abstract:The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 5 publications
1
8
0
Order By: Relevance
“…[3,12] In this study, various forms of the coronoid process, condyle and sigmoid notch were evaluated with the support of panoramic radiographs. The most common shape of the coronoid process detected was triangular followed by round with male predominancy seen maximum in the age range of 30-40 years in the population of Bengaluru which is in accordance with Column totals 300 300 600 the studies conducted by Sahithi et al in the South Indian population [7] and Shakya et al, [9] Sudha et al, [13] and Pradhan et al [14] among the South Indian populations. Our comment regarding the shape of coronoid population was totally opposing to the studies conducted by Tapas et al [12] among the North Indian population and Kadam et al [15] among the West Indian population where according to them hook/beak shape to be common followed by the triangular shape.…”
Section: Discussionsupporting
confidence: 72%
“…[3,12] In this study, various forms of the coronoid process, condyle and sigmoid notch were evaluated with the support of panoramic radiographs. The most common shape of the coronoid process detected was triangular followed by round with male predominancy seen maximum in the age range of 30-40 years in the population of Bengaluru which is in accordance with Column totals 300 300 600 the studies conducted by Sahithi et al in the South Indian population [7] and Shakya et al, [9] Sudha et al, [13] and Pradhan et al [14] among the South Indian populations. Our comment regarding the shape of coronoid population was totally opposing to the studies conducted by Tapas et al [12] among the North Indian population and Kadam et al [15] among the West Indian population where according to them hook/beak shape to be common followed by the triangular shape.…”
Section: Discussionsupporting
confidence: 72%
“…Nirmale et al had studied 84 dry mandible for various parameter including coronoid process and found triangular 109 side followed by hook in 47 side and rounded in 12 [6]. S pradhan et al showed most common shape of coronoid process was triangular (46.73%) then rounded (35.3%) and least hook shape in 17.93% [7].…”
Section: Discussionmentioning
confidence: 99%
“…According tothe studies conducted by Sahithi et al [6], Shakya et al [7], Sudha et al [2] and Pradhan et al [8]among the South Indian populations, in case of male and female,the most common shape of the coronoid process detected was triangular followed by round with male pre-dominancy. In their study Sheela D. Kadam et al [11] observed that most common shape of coronoid process was triangular in both sex (62.5% in male and 67.08% in female).…”
Section: Discussionmentioning
confidence: 96%
“…Various scholars in their studies have noted different sequences of prevalence of shapes. Tanveer A et al [3], Nirmale et al [4] observed that triangular shape of coronoid process were most prevalent which were followed by hooked and rounded shapes respectively in their respective studies.Vipul et al [5], Sahithiet al [6], Shakya et al [7], Sudha et al [2] and Pradhan et al [8] have concluded that most common shape of coronoid process was triangular only in their studies also, but, it was followed by rounded and hooked shapes respectively. It is very useful for anthropological and forensic studies to know about the prevalence of shapes of coronoid process [7].…”
Section: Introductionmentioning
confidence: 96%